OPEN VEINS OF LATIN AMERICA IN THE ANTHROPOCENE: A BIOPHYSICAL STUDY ON FOREIGN TRADE - Infante-Amate , Juan (2020)
Latin America has long played a key role in the global provision of natural resources. Most of the continent’s economies are low-value, primary-product net exporters while they import manufactured goods at a high price. There is a general agreement among researchers from various fields that this pattern of specialize trade has very negative implications for economic development, the environment, and the local population wellbeing. Yet, there is little empirical evidence on the total contribution of Latin America to the rest of the world’s regions. Drawing on Material Flow Accounting methodology, this paper estimates physical and monetary trade in 16 Latin American economies between 1900 and 2016.